P247 Umeclidinium/vilanterol (UMEC/VI) versus mono-bronchodilator therapy in steroid-free GOLD B patients with chronic obstructive pulmonary disease (COPD): the EMAX trial. (December 2018) - Jones, PW; Maltais, F; Kerwin, E; Bjermer, L; Watkins, ML; Tombs, L; Naya, I; Boucot, I; Lipson, D; Compton, C; ,
Abstract : Introduction: Long-acting muscarinic antagonist/long-acting β2 -agonist (LAMA/LABA) combination therapy is more effective than monotherapies for improving lung function, breathlessness and health status, in patients with moderate-to-severe COPD (Oba et al. Thorax 2016:71;15–25). Current Global initiative for chronic Obstructive Lung Disease (GOLD) strategy highlights that first-line maintenance therapy in symptomatic GOLD B patients is LAMA or LABA monotherapy (GOLD 2018 report). The Early MAXimal bronchodilation for improving COPD stability (EMAX) trial aims to compare the efficacy and safety of UMEC/VI (LAMA/LABA), UMEC (LAMA) and salmeterol (SAL [LABA]) in symptomatic, steroid-free GOLD B patients with COPD (study 201749; NCT03034915 ) to inform the positioning of dual versus monotherapy within treatment guidelines for GOLD B patients. Methods: EMAX is a 24 week, multicentre, double-blind, double-dummy, parallel-group study. Patients (n=2, 431) were randomised 1:1:1 to UMEC/VI 62.5/25 mcg, UMEC 62.5 mcg or SAL 50 mcg (figure 1). Patients were required to be aged ≥40 years, current/former smokers (≥10 pack-years), with a forced expiratory volume in 1 s (FEV1 )/forced vital capacity ratio <0.70, post-salbutamol FEV1 ≥30% to≤80% predicted, COPD Assessment Test (CAT) score ≥10, and ≤1 moderate and no severe exacerbations in the past year. Randomisation was stratified by maintenance bronchodilator use (none or one permitted) at screening. The primary endpoint is trough FEV1 with UMEC/VI versus UMEC at Week 24. Secondary endpoints include comparisons of UMEC/VI with UMEC and SAL for other spirometry measures and patient-reported outcomes (transition dyspnoea index [TDI], Evaluating Respiratory Symptoms-COPD [E-RS], SGRQ, CAT), rescue medication use and COPD stability assessed using time-to-first (TTF) exacerbation and TTF clinically important deterioration (CID). Safety and tolerability are assessed. The study is powered for comparisons of trough FEV1 and TDI. Conclusions: EMAX is the largest study to date investigating the efficacy of LAMA/LABA versus monotherapy in inhaled corticosteroid-naïve symptomatic GOLD B patients, and the first prospective study to explore the impact of these regimens in maintenance-naïve patients (a pre-specified subgroup) and assess COPD stability using the CID. The study has completed; upon completion of data analysis, the results should help clarify when, and in which population, LAMA/LABA should be initiated as first-choice maintenance therapy. Funding: GSK (study 201749). Please refer to page A268 for declarations of interest related to this abstract.